Educational Institutions in Uzbek Society: Status and Impact on Social And spiritual Life (Early 1870s - 90s of the XX century) - N.Q.Ismatova (Periodica Journal, 2022)
This article covers the centenary education system in the country - from the early 1870s to the 1990s, with its maturity and problems in this area, based on analytical materials and sources. It also analyzes the socio-economic environment of the studied society and its impact on the education system and, as a result, the views of the indigenous population on the education of their children, their willingness to study in new and old schools and the existing socio-educational environment
Keywords: Turkestan; Reformation; public education; education